Planning for Ecosystem Services in Cities - Geneletti, Davide; Cortinovis, Chiara; Zardo, Linda; Esmail, Blal Adem.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access book presents current knowledge about ecosystem services (ES) in urban planning, and discusses various urban ES topics such as spatial distribution of urban ecosystems, population distribution, and physical infrastructure properties. The book addresses all these issues by: i) investigating to what extent ecosystem services are currently included in urban plans, and discussing what is still needed to improve planning practice; ii) illustrating how to develop ecosystem services indicators and information that can be used by urban planners to enhance plan design; iii) demonstrating the application of ES assessments to support urban planning processes through case studies; and iv) reflecting on criteria for addressing equity in urban planning through ecosystem service assessments, by exploring issues associated with the supply of, the access to and demand for ES by citizens. Through fully worked out case studies, from policy questions, tobaseline analysis and indicators, and from option comparison to proposed solutions, the book offers readers detailed and accessible coverage of outstanding issues and proposed solutions to better integrate ES in city planning. The overall purpose of the book is to provide a compact reference that can be used by researchers as a key resource offering an updated perspective and overview on the field, as well as by practitioners and planners/decision makers as a source of inspiration for their activity. Additionally, the book will be a suitable resource for both undergraduate and post-graduate courses in planning and geography.
Chapter1. Introduction -- Chapter2. A review of ecosystem services in urban plans -- Chapter3. A review of ecosystem services in urban climate plans -- Chapter4. Developing ecosystem service information for urban planning -- Chapter5. Applying ecosystem services in urban planning: a case study -- Chapter6. Towards equitable distribution of ecosystem services in cities -- Chapter7. Conclusions.
Keywords: Physical geography; Climatology; Urban ecology (Biology).; Human geography; Earth System Sciences; Climate Sciences; Physical Geography; Urban Ecology; Human Geography